126 CASE PRESENTATION OF RENAL CELL CARCINOMA METASTATIC TO THE PITUITARY GLAND. Issue 1 (1st January 2007) - Jones, J. R.; Hamilton, R. D.
Abstract : Purpose: To present a case of renal cell carcinoma metastatic to the pituitary gland. Methods: A 68-year-old white male who previously underwent a right radical nephrectomy for renal cell cancer presented with a 2-month history of diplopia and fatigue. Physical examination revealed an enlarged left pupil and a left-sided sixth nerve palsy. MRI showed a pituitary mass. On laboratory analysis, levels of TSH, T4, ACTH, cortisol, LH, and testosterone were all decreased. The patient underwent a transsphenoidal hypophysectomy. Results: The specimen submitted to pathology was a 1.8 × 1.2 × 1.7 cm pituitary mass. Final pathologic results revealed the tumor to be metastatic renal cell carcinoma, clear cell type. CT chest/abdomen/pelvis and bone scan showed no other evidence of metastatic disease. The patient subsequently underwent gamma-knife radiosurgery, with a total dose of 1, 600 cGy delivered. Follow-up scans continue to show no evidence of disease. The patient was also placed on replacement therapy for multiple hormonal deficiencies with a good response. Conclusions: Metastatic disease in the pituitary gland accounts for approximately 1% of all pituitary tumors. Renal cell carcinoma metastatic to the pituitary is even more uncommon as by far the most common malignant tumors involving the pituitary gland are breast and lung cancer. Metastatic disease with renal cell carcinoma is almost always associated with diffuse involvement. Therefore, recurrent renal cell carcinoma presenting as an isolated pituitary metastasis is extremely rare. The majority of pituitary metastases are clinically silent; however, diabetes insipidus is the most common manifestation in patients with symptomatic disease. Metastatic renal cell carcinoma to the pituitary gland, in contrast, is more frequently associated with the unique features of anterior pituitary dysfunction and visual disturbances. MRI is the imaging procedure of choice, with several imaging characteristics being more indicative of pituitary metastases than pituitary adenomas. Multiple treatment modalities are available for pituitary metastases, including resection, radiation therapy, and chemotherapy. Transsphenoidal surgical resection is the mainstay of therapy. In most series, adjuvant radiation therapy has been used, and radiosurgery also plays a significant role. Chemotherapeutic agents have been widely used in the past with limited success. Recently, however, the discovery of the association of vascular endothelial growth factor with the von Hippel-Lindau protein has allowed the development of several antiangiogenic agents, which are likely to significantly improve the treatment of metastatic renal cell carcinoma.